GE_GERICHTE C/10516/2017 vom 2. Oktober 2017 - GE Cour de justice (2017)
BAIL À LOYER ; EXPULSION DE LOCATAIRE ; CONTRAT-CADRE ; NOTORIÉTÉ ; SOMMATION ; EXÉCUTION(PROCÉDURE) | CPC.257; CPC.151; CO.257d;